Evaluation of α-Amylase Inhibitory Activity, Molecular Modeling, Total Antioxidant and Theoretical Studies of Novel Schiff Base Transition Metal Complexes - Sudha, A.; Arulmozhi, S.; Askar Ali, S.J. (Asian Journal of Chemistry, 2020)
By condensing pyrene-1-carbaldehyde and 4-aminoantipyrine, a Schiff base ligand, (Z)-1,5-dimethyl-2-phenyl-4-((pyren-1-ylmethylene)-amino)-1H-pyrazol-3(2H)-one and its Cu(II), Ni(II), Co(II) and Zn(II) complexes have been synthesized. The ligand and its metal complexes were characterized by FT-IR, UV-visible, 1H & 13C NMR, ESI-mass spectra and elemental analysis. The antidiabetic and antioxidant activities of the synthesized Schiff base ligand and its metal complexes were studied. The molecular docking study of human pancreatic α-amylase (PDB: 1HNY). Furthermore, Theoretical analysis of geometry optimization and frontier molecular orbital analysis (HOMO-LUMO) was accomplished by density functional theory using B3LYP/3-21G*++ basis sets to understand the chemical stability of the synthesized ligand and their metal(II) complexes.